Preventable Trauma Deaths Rate (PTDR)—Analysis of Variables That Shape Its Value With Patterns of Errors Contributing to Trauma Mortality. Fifteen Years of Experience Based on the Example of a Polish Specialist Regional Hospital - Witkowski, Andrzej; Jakubaszko, Juliusz; Mańka, Rafał; Witkowski, Tomasz (Frontiers in Sustainable Cities, 2020)
This analysis is based on a review of 224 out of 323 cases of trauma deaths in Regional Specialist Hospital of Grudziądz during the period of 2003-2017. From the objective statistical parameters described, we evaluate the level of quality of State Emergency Medical System in Poland. In the daily struggle of saving lives the question always remains: what could we have done differently? Better? More effectively? To answer this question we have to examine our emergency procedures and activities. Were they correct and effective? This documentation shows us not only a statistical picture of the injuries sustained by trauma victims, but also presents a dynamic reconstruction of events as well as the pathophysiology of dying. When we view all this material as a complete picture, we see that it provides the opportunity to assess the accuracy of judgment, especially during the critical moments of diagnosis and subsequent treatment of the casualties. Not only did we describe the anatomic results of injuries, including rankings to proper regions of the body, we also reconstructed the pathophsiology of dying such as: airway obstruction – suffocation, bleeding – exsanguination, or severe complications as ARDS, pulmonary emboli, thrombosis of intracranial vasculature, and fatal, irreversible organ damage. We checked operating procedures that had been done, and those which should have been done to give the patient a chance for survival but weren’t due to wrong decisions. We have demonstrated that the element of time is critically important in diagnosing and implementing treatment of patients with major injuries; further, we have enumerated the potential complications, time errors, missed injury and general mismanagement as professional risks for the emergency team. We have determined that almost half of all trauma deaths occur within the first two days following major injury with most of those occurring within the first 6 hours of hospitalization. The other deaths – ‘late deaths’ – are the result of unsuccessful treatment or the development of complications in ICU.